How do elections affect you according to your political affiliation? - Silva, Aigla Gomes da (2023)
Highly contested elections, in which the outcome is not predictable, can amplify responses from the voters from either the winning or the losing side. We expect a change in financial behavior as a result after the election, where the voters of the elected candidate increase their purchases, especially of durable goods, in relation to the other voters. This increased consumption of durable and nondurable goods was captured in the corresponding credit operations. We used data from 2.3 million people provided by a Brazilian financial institution with presence throughout the country, referring to the period of highly contested Brazilian elections of 2018 and 2022. We show that voters residing in cities with a higher proportion of votes for the winning candidate increased their expenses after the elections, increasing their credit portfolio in real estate, vehicles, and general consumption. This behavior was consistent whether the winner was a left-wing or a right-wing politician. This behavior is relevant because it has an impact on the financial activity city-wide and, by extension, throughout the country.